The Analysis of Clinical sign, Mortality and Histopathology of Cantang Grouper Infected with VNN in Recirculating Aquaculture System - Susanti, Ni Putu Nadya; Antara, Kadek Lila; Mahardika, Ketut; Setiabudi, Gede Iwan (Advances in Tropical Biodiversity and Environmental Sciences; Vol 6 No 3 (2022): ATBES, 2022)
Hybrid grouper is a variety of grouper that has become increasingly popular in recent years. The development of grouper cultured in Indonesia utilizing the Recirculating Aquaculture System (RAS) is currently underway; nevertheless, fish cultured in the RAS system continue to struggle with infectious diseases, one of which is VNN (viral nervous necrosis) infection caused by piscine betanodavirus. The purpose of this study was to know the clinical sign, mortality, and histopathology of cantang grouper ( Epinephelus fuscoguttatus x E. lanceolatus ) infected with VNN in RAS. Fish samples were obtained from the hatchery using RAS. This research uses a mixed methods approach and the type of research used is exploratory research. The parameters observed were clinical signs, mortality, and histopathology. Water quality, including temperature, DO, salinity, and pH at the time of VNN infection, was used as secondary data. The results showed that clinical signs of sick fish were weakness, staying at the bottom of the rearing tank, decreased appetite, swimming with the stomach facing up and the body dark in color. Fish mortality occurred for ± 10 days with a peak of mortality reaching 26.86 ± 7.45% on day 9 from initial signs. Histopathology result, diseased fish showed vacuolization in the brain and retina of the eye.